Dual-Band Band-Stop Filter using Multiple Hexagonal Microstrip Line for Chipless RFID Sensor - Suwalak, Rattapong; Lertsakwimarn, Kittima; Lertwiriyaprapa, Titipong; Phongcharoenpanich, Chuwong; Torrungrueng, Danai (My University, 2023)
The dual-band band-stop filter using a hexagonal-shape microstrip line is presented in this paper. The chipless RFID with the band-stop filter used to determine the relative permittivity of material under test and identify characteristic based on the unique responded signal from the chipless RFID sensor. This paper proposed the multiple microstrip line structure with a quarter-wavelength transformer to generate an identification (ID) code, i.e., ID-01, ID-10, and ID-11 at the center frequency of 2.2 GHz and 2.7 GHz. From the results, the proposed chipless RFID sensor can be identified and determined the relative permittivity of the LWC.
Keywords: band-stop filter; chipless; open-circuited stub; quarter-wave transformer; RFID sensor